2012
DOI: 10.1182/blood-2012-05-423210
|View full text |Cite
|
Sign up to set email alerts
|

The gene therapy journey for hemophilia: are we there yet?

Abstract: AbstractSince the isolation and characterization of the genes for FVIII and FIX some 30 years ago, a longstanding goal of the field has been development of successful gene therapy for the hemophilias. In a landmark study published in 2011, Nathwani et al demonstrated successful conversion of severe hemophilia B to mild or moderate disease in 6 adult males who underwent intravenous infusion of an adeno-associated viral (AAV) vector expressing factor IX. These 6 subjects have now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 58 publications
2
35
0
3
Order By: Relevance
“…The ultimate goal of such efforts is to continue to improve AAV vector technology that would help decrease the effective vector dose required for achieving therapeutically relevant transgene expression levels. These technological advancements are also likely to help alleviate potential clinical concerns associated with vector dosedependent toxicity (38,39). In summary, rational engineering of capsid-glycan receptor interactions is a promising approach toward continued improvement of the preclinical/clinical pipeline of AAV vectors for gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal of such efforts is to continue to improve AAV vector technology that would help decrease the effective vector dose required for achieving therapeutically relevant transgene expression levels. These technological advancements are also likely to help alleviate potential clinical concerns associated with vector dosedependent toxicity (38,39). In summary, rational engineering of capsid-glycan receptor interactions is a promising approach toward continued improvement of the preclinical/clinical pipeline of AAV vectors for gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[14] oraz rozszerzenia wskazań do terapii genowej hemofilii B o pacjentów zakażonych ludzkim wirusem niedoboru odporności (HIV, human immunodeficiency virus) i wirusem wątroby typu C (HCV, hepatitis C virus) oraz tych, u których wykryto przeciwciała przeciwko AAV. W ostatnim przypadku rozwiązaniem może być zastosowanie pustych kapsydów AAV2, które chronią kapsydy AAV8 zawierające gen kodujący FIX, poprzez związanie obecnych w krwiobiegu pacjenta przeciwciał przeciwko AAV [15].…”
Section: Terapia Genowa W Hemofilii Bunclassified
“…Bardzo interesujące są też badania nad alternatywnymi wektorami, na przykład lentiwirusowymi. Kolejnym krokiem w rozwoju badań nad terapią genową powinno być zapoczątkowanie prób klinicznych u pacjentów z hemofilią A. Niestety, dziś wiadomo, że o sukces w terapii genowej hemofilii A będzie znacznie trudniej niż w hemofilii B -przede wszystkim z powodu wielkości cDNA FVIII oraz silniej odpowiedzi immunologicznej ludzkiego organizmu wobec FVIII [14].…”
Section: Terapia Genowa W Hemofilii Bunclassified
“…Using the standard gene-therapy approach, researchers have shown that they can achieve long-term expression of factor IX in adults with haemophilia B at sufficiently high levels to convert the bleeding disorder into a mild disease (see page S160). There has so far been no reported evidence of inhibitor formation in the small number of human participants in clinical trials for this viral therapy 6 . Still, the standard form of liver-targeted gene therapy carries a range of potential complications, including the risk of harmful mutations and of the body mounting an immune response against the viral vectors used to carry the correct forms of the defective genes responsible for haemophilia.…”
Section: Inhibitory Controlmentioning
confidence: 99%